Frank Herbert's "Dune" - Kennedy, Kara. author. aut Link
XI, 113 p. 6 illus. in color.
Keywords: This book offers a critical study of Frank Herbert’s Dune (1965), the world’s bestselling science fiction novel. Kara Kennedy discusses the novel’s exploration of politics and religion, its influential ecological messages, the focus on the human mind and consciousness, the complex nature of the archetypal hero, and the depiction of women’s influence and control. In Dune, Herbert demonstrated that sophistication, complexity, and a multi-layered world with three-dimensional characters could sit comfortably within the science fiction genre. Underneath its deceptively simple storyline sits a wealth of historical and philosophical contexts and influences that make it a rich masterpiece open to multiple interpretations. Kennedy’s study shows the continuing relevance of the novel in the 21st century due to its classic themes and its concerns about the future of humanity, as well as the ongoing nature of issues such as ecological disruption and conflictsover resources and religion. Kara Kennedy is a researcher, writer, and educator in the areas of science fiction, digital literacy, and writing. She is an avid scholar of Dune who has lectured and published on various topics including world-building. She posts literary analyses of Dune for a mainstream audience on her blog DuneScholar.com. She is the author of Women’s Agency in the Dune Universe: Tracing Women’s Liberation through Science Fiction (Palgrave Macmillan 2021).